Using preceptors to improve nursing students' clinical learning outcomes: A Malawian students' perspective - Ellemes Phuma-Ngaiyaye, PhD, RN, RM; Thokozani Bvumbwe, MCur (CHN); Mep Coretta Chipeta, BScN, RN, RM (Elsevier, 2017)
Objective: Clinical environment remains an important aspect in the development of student's competence, confidence and fulfillment of their expected learning outcomes. Preceptors and clinical teachers play a significant role in preparing students to achieve their professional goals through continuous support and resource provision. This study explored the students' perception of using clinical preceptors to improve their clinical learning outcomes. Methods: The researchers used semi structured interviews to collect qualitative data. A total of 48 students were purposively and conveniently sampled from 8 hospitals to participate in the study. Content analysis was used to analyse the data. Findings: Two themes emerged from the study findings namely: creating a positive clinical learning environment and facilitating academic clinical collaboration. Conclusions: The findings of the study revealed that students gained more confidence and competence in clinical practice when supported by preceptors as well as achieved clinical learning outcomes. These findings suggest the need to train more clinical preceptors for improvement of students' clinical learning outcomes.